Knowledge assessment of Cienfuegos´ health workers on human toxocariasis. - Martina S. Jiménez Suárez; Blanca Elena Duménigo Ripoll (Medisur)
Background: Human toxocariasis is one of the most worldwide extended zoonosis. It mainly affects children and it is not always well known by medical staff. Objective: To assess knowledge of Cienfuegos´s health workers on human toxocariasis. Method: A descriptive cross-sectional study was developed from May to September 2005 and a survey was applied to a total sample of 51 doctors through a randomized, stratified sampling. In addition to consider professional category, years of experience and knowledge on zoonosis, we analyzed different aspects the form the variable general knowledge on human toxocariasis. Findings: We could develop a knowledge assessment on toxocariasis in Cienfuegos´ doctors. These findings were compared with surveys in other countries. There is not history of this kind of research in Cuba. Conclusions: Cienfuegos´ doctors knowledge on toxocariasis diagnosis, transmission, and prevention and not satisfactory except for clinic and treatment.